Anti-tumor activity and mechanism of oligoclonal hepatocellular carcinoma tumor-infiltrating lymphocytes in vivo and in vitro - Wang, Wen-Chao (Cancer Biol Ther, 2019)
Objective: To explore a method for culturing hepatocellular carcinoma and tumor-infiltrating lymphocytes (HCC-TIL) and investigate the mechanism of TIL in killing tumors. Methods: The distribution of regulatory T cells (Treg) in HCC was detected by immunohistochemistry. Conventional TIL and oligoclonal TIL were isolated by the traditional method of enzyme digestion combined with mechanical treatment for whole HCC and micro HCC tissue block culturing method. MTT was used to compare the killing activity of TIL. Flow cytometry was used to analyze the proportion of CD8(+) T cells and Treg cells in TIL. Tumor-bearing mice were established, and TIL adoptive immunotherapy was performed. Results: Treg cells were mainly distributed in the stroma of HCC. In vitro experiments showed oligoclonal TIL had higher cytotoxicity to tumor cells which negatively correlated with the proportion of Treg cells. In vivo experiments showed oligoclonal TIL had a higher anti-tumor effect. IFN-γ in peripheral blood and the positive rate of intratumoral lymphocytic infiltration in oligoclonal TIL group were both higher. TGF-β and IL-10 in peripheral blood and the positive rate of intratumoral FoxP3 and IL-17 were both lower than those in conventional TIL group. Conclusion: The oligoclonal TIL culture method could obtain TIL with higher purity, and cytotoxicity to tumor cells was associated with Treg cells. The oligoclonal TIL had cytotoxicity to autologous HCC cells and significant inhibitory effect on the growth of transplanted tumors. The mechanism might be associated with the inhibition of Treg cells proliferation, increase of IFN-γ secretion, and decrease of TGF-β, IL-10, and IL-17 secretion.